The complications of male hypogonadism: is it just a matter of low testosterone? - Munari, Elisabetta Veronica; Amer, Myriam; Amodeo, Alessandro; Bollino, Ruggiero; Federici, Silvia; Goggi, Giovanni; Giovanelli, Luca; Persani, Luca; Cangiano, Biagio; Bonomi, Marco (Frontiers in Endocrinology, 2023)
The history of diagnosing hypogonadism and hypotestosteronemia shows us the many steps that were necessary to achieve our current knowledge and the ability to improve these patients’ well-being. Moreover, so far, criteria for diagnosing hypotestosteronemia varies according to the underlying condition, and according to the consensus or guideline adopted. Besides several signs and symptoms, many complications, such as osteoporosis, metabolic alterations, as well as cardiovascular disordersare are also associated with low testosterone levels. However, data are often conflicting regarding the severity, timing or even the real clinical relevance of these complications, although these studies often lack essential information such as gonadotropins levels or the underlying cause of hypogonadism. The present review focus on the complications of male hypogonadism according to the cause of testosterone deficiency, highlighting the lack of information found in many studies investigating its effects. We thereby stress the necessity to always perform a complete evaluation of the type of hypogonadism (including at least gonadotropins and secondary causes) when investigating the effects of low testosterone levels.